2022
DOI: 10.3390/diagnostics12123037
|View full text |Cite
|
Sign up to set email alerts
|

ECG and Biomarker Profile in Patients with Acute Heart Failure: A Pilot Study

Abstract: Background: Biomarkers, electrocardiogram (ECG) and Holter ECG are basic, accessible and feasible cardiac investigations. The combination of their results may lead to a more complex predictive model that may improve the clinical approach in acute heart failure (AHF). The main objective was to investigate which ECG parameters are correlated with the usual cardiac biomarkers (prohormone N-terminal proBNP, high-sensitive cardiac troponin I) in patients with acute heart failure, in a population from Romania. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Several recent studies and two meta-analyses confirmed the relevance of the measurement of cardiac-specific biomarkers in patients presenting to the ED with acute dyspnea or AHF [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. In particular, cardiac NPs have already been included in the initial standard ED diagnostic workup of patients with dyspnea [76].…”
Section: Role and Advantages Of Poct Methods For Cardiac Troponin In ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Several recent studies and two meta-analyses confirmed the relevance of the measurement of cardiac-specific biomarkers in patients presenting to the ED with acute dyspnea or AHF [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. In particular, cardiac NPs have already been included in the initial standard ED diagnostic workup of patients with dyspnea [76].…”
Section: Role and Advantages Of Poct Methods For Cardiac Troponin In ...mentioning
confidence: 92%
“…According to the most recent clinical studies, high levels of both cardiac-specific biomarkers (i.e., NPs and hs-cTn) in AHF patients are consistently associated with an increased risk of morbidity and mortality, due to the combined presence of a severe reduction in cardiac function and myocardial injury (or even ACS) [56,76,77,80,87,88,[100][101][102]104]. The relevant effect on mortality and MACE in patients admitted to the ED with AHF for several days (or even months), associated with the progressive increase in both specific cardiac biomarkers, has recently been well illustrated in the particular clinical conditions related to COVID-19 infection [105][106][107][108][109][110].…”
Section: Role and Advantages Of Poct Methods For Cardiac Troponin In ...mentioning
confidence: 99%
“…In vivo, natriuretic peptides counteract the water and sodium retention caused by angiotensin and endothelin by dilating blood vessels, inhibiting ventricular remodeling, and preventing cardiac decline. [ 18 ] In response to the over-activation of the sympathetic nervous system and RAAS, the “Golden Triangle” of drugs has emerged to improve ventricular remodeling and includes angiotensin-converting enzyme inhibitors or angiotensin receptor antagonists, beta-blockers, and aldosterone receptor antagonists; however, therapeutic effects have been limited. [ 19 ] Further treatment options that can improve cardiac function, reduce circulatory congestion and clinical symptoms, and ensure adequate organ blood supply [ 20 ] are urgently needed to treat recurrent acute episodes of chronic HF and reduce the rates of rehospitalization and mortality and improve overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Chetran 2022, Kang 2017, and Kanukurti 2020 achieved the highest score (8, low risk of bias). [19][20][21] None of the studies had a score ≤ 5, indicating a high risk of bias. A funnel plot (Fig.…”
Section: Assessment Of Quality and Publication Biasmentioning
confidence: 99%